Integrating Traditional Authority into Electoral Governance: Lessons from the Bida Emirate Experience, Nigeria - Gana, Idrees Mahmud; Umar, Sakina Nna (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
Traditional authority remains a central component of governance and policy mediation across Africa, where culturally grounded legitimacy often complements formal state institutions. This study examines how traditional institutions contribute to electoral governance through the case of the 2023 general elections in the Bida Emirate, Niger State, Nigeria. Guided by Hybrid Governance Theory and Institutional Pluralism, the research explores how indigenous authority structures interact with formal institutions to promote democratic legitimacy, peace, and civic participation. Using a descriptive survey design, data were collected from 299 respondents and analyzed through descriptive and inferential statistics, including the Chi-square test. The analysis reveals that traditional leaders in the Bida Emirate played significant roles in electoral peacebuilding through dialogue, community sensitization, and collaboration with security agencies. Findings highlight how traditional legitimacy complements formal electoral institutions by fostering trust, moral authority, and compliance with peaceful conduct during elections. The study contributes to the policy integration of traditional institutions by demonstrating that hybrid governance can enhance electoral credibility and conflict prevention in plural political environments. It recommends that electoral management bodies institutionalize structured consultations with traditional councils as part of election planning, voter education, and dispute resolution mechanisms. In doing so, African electoral systems can strengthen democratic legitimacy by embedding indigenous authority within the architecture of public administration and governance reform.